Comparative efficacy of kneading massage and pulsed mode ultrasound in the management of chronic knee osteoarthritis - Ojoawo, Adesola O.; Fatai, Wasiu Abiodun (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Osteoarthritis of the knee is the most common presentation of osteoarthritis with prevalence between 12% and 35% of general population and is considered the leading cause of musculoskeletal disability in the elderly population worldwide. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The study compared efficacy of kneading massage and pulsed ultrasound on pain, joint stiffness and difficulty in knee osteoarthritis (KOA). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Fifty subjects with radiological evidence of KOA participated in the study. They were randomly allocated into kneading massage group (KMG) (25) and Ultrasound group (USG) (25). KMG received kneading massage for 7 minutes while USG received pulsed mode ultrasound for 15 minutes. Treatment was twice in a week for six weeks. Pain intensity (PI), joint stiffness and difficulty were assessed pre, 3rd and 6th weeks of treatment session with semantic differential scale and WOMAC. The data were analyzed using descriptive and inferential statistics, alpha level was set at 0.05 <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. There was a significant difference in present PI (F=11.45,P=0.001) and stiffness (F= 11.32, P=0.003) in USG. There was a significant reduction in PI (F=7.95, P=0.001) and joint stiffness (F=8.86, P=0.003) in KMG. At the 6th week, there was a significant differences in PI (t=12.23,P=0.000) and stiffness (t=8.08, P=0.000) when USG (3.00+0.4, vs 7.14+ 1.49) was compared with KMG (3.16+0.5 vs 7.50+1.5). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Ultrasound (US) and kneading massage (KM) reduced PI and joint stiffness of KOA effectively; however US reduced PI than KM while KM reduces joint stiffness than US.